Plan de marketing para posicionar a molinos san gabriel ubicado en el barrio san felipe, parroquia Eloy Alfaro, cantón Latacunga, provincia de Cotopaxi - Chasiloa Cando, Jessica Aracelly (2015)
This research was conducted in order to make a marketing plan to position the company San Gabriel, with the aim of improving their recognition and growth in a desired future. It is noteworthy that very relevant information was collected for the researcher and the company, because they proceeded to carry out a field study to determine the key factors that prevented better positioning the company. Therefore, it was established that the company SAN GABRIEL is highly competitive companies like MOLINOS OROBLANCO, PRODICEREAL and MOLINOS POULTIER, this last was found in that market and it´s preventing the growth and customer loyalty for the company San Gabriel….